The pharmacology of the oppressed: decolonizing Cannabis science in higher education - Cross, Brandie Makeba (Frontiers in Education, 2025)
This analysis explores the potential of Paulo Freire’s pedagogical framework to decolonize Cannabis science education, focusing on the dynamic relationship between the oppressed and the oppressor within the context of Cannabis criminalization and legalization. It examines the historical, cultural, and racialized dimensions of Cannabis policies and their implications for marginalized communities, particularly American Indigenous, Black and Latinx populations. Drawing on Freire’s critique of traditional, hierarchical models of education, the paper argues for a dialogical, participatory approach to Cannabis education that fosters critical consciousness and social transformation. The analysis discusses the role of Cannabis science in perpetuating or challenging systemic injustices and proposes a curriculum that integrates diverse perspectives from biology, sociology, and history. By incorporating Freire’s principles, Cannabis education can empower students to critically engage with both the science of Cannabis and the broader societal impacts of its criminalization and commercialization. The paper concludes by emphasizing the need for Cannabis education to not only teach the science of Cannabis but to also challenge inequities and promote social justice, advocating for a holistic, interdisciplinary curriculum that empowers students to become agents of change in Cannabis policy and practice.